Physiological parameters of professional football players in teams of various levels - Stojmenovic, D.; Stojmenovic, T. (Pedagogy of Physical Culture and Sports, 2023)
Background and study aim. Soccer is a demanding sport which, in addition to technical and motor characteristics, also requires exceptional functional abilities of athletes to play at a high level. The aim of this study: 1) To analyze the disparities in physiological parameters among professional soccer players in teams of varying levels. 2) To explore potential connections between team ranking positions and the physiological attributes of professional soccer players.